2002
DOI: 10.4319/lo.2002.47.3.0848
|View full text |Cite
|
Sign up to set email alerts
|

A model of sediment transport over an intertidal transect, comparing the influences of biological and physical factors

Abstract: This paper compares modeled biotic and physical effects on intertidal sediment transport, using parameterizations that are based on laboratory and field experiments. A one-dimensional model of an intertidal transect is constructed. The model is aligned cross shore and includes movement of water and suspended sediment. Within the model, tidal currents cause erosion, and bioturbation by the clam, Macoma balthica, alters the erodability of the bed sediment. The concentration of chlorophyll a in the surface sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 24 publications
5
39
0
Order By: Relevance
“…Such an approach has been useful in explaining salt marsh development (Temmerman et al 2007). Studies by Le Hir et al (2007) and by Wood & Widdows (2002) have included the temporal and seasonal dynamics of both MPB and macrofauna effects and arrive at similar qualitative and quantitative conclusions. Both studies conclude that MPB effects are fairly well understood, relatively easy to model and overall stabilising.…”
Section: Intricate Interactionsmentioning
confidence: 86%
“…Such an approach has been useful in explaining salt marsh development (Temmerman et al 2007). Studies by Le Hir et al (2007) and by Wood & Widdows (2002) have included the temporal and seasonal dynamics of both MPB and macrofauna effects and arrive at similar qualitative and quantitative conclusions. Both studies conclude that MPB effects are fairly well understood, relatively easy to model and overall stabilising.…”
Section: Intricate Interactionsmentioning
confidence: 86%
“…Observations from this system suggest that the decline is potentially caused by increased grazing pressure by benthic animals . The effects that macrobenthic grazers have on the interaction between diatoms and sedimentation have been investigated in a number of field and model studies (Wood and Widdows 2002, Paarlberg et al 2005, Le Hir et al 2007, revealing that herbivore grazing can influence sediment dynamics both directly by feeding and indirectly through bioturbation. Hence, intertidal mudflats provide a unique opportunity to investigate the effects of increasing top-down control in spatially self-organized ecosystems and to test the effects of grazing on selforganization and landscape formation in manipulative experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The mediation of the erodibility of fine-grained sediments by both microzoobenthos and macrozoobenthos has for example now been described for several species and field sites (e.g., Nowell et al, 1981;Paterson, 1989;Yallop et al, 1994;Widdows and Brinsley, 2002). In spite of these studies, little is still known about the net-effect of biotic processes with respect to mudflat sedimentation and budgets of fine-grained sediments although a few modelling studies have indicated that this effect may potentially be large (Wood and Widdows, 2002;Widdows et al, 2004;Lumborg et al, in press).…”
Section: Introductionmentioning
confidence: 99%